Strategi Dan Program Puri Sayan sebagai Daya Tarik Wisata Heritage di Desa Sayan, Kecamatan Ubud, Kabupaten Gianyar, Bali - Ratih Arthanovia; I Made Adikampana (JURNAL DESTINASI PARIWISATA, 2020)
This study focuses on studying the planning of Puri Sayan Ubud as a heritage tourist attraction in Sayan Village, which is also intended to realize one of the Village missions, namely to become a Tourism Village in order to improve the welfare of local communities. This study has a limited scope in identifying existing conditions of tourism in Puri Sayan and Puri Sayan planning as a heritage tourist attraction. The data collection techniques in this study are observation, interviews, and documentation. Data analysis techniques used are qualitative descriptive and SWOT analysis that refers to tourism product components 4A. The results of this study are in the form of strategies and programs produced by SWOT analysis after identifying existing conditions that refer to tourism product components 4A. The results of this study is about the main planning of Puri Sayan Ubud as an Attraction of Heritage Tourism by designing various programs such as attraction and management that are designed based on the strategy of the result of SWOT analysis that has been done. Keyword: Heritage, Heritage Tourism, Planning, Puri